Assessment of Procalcitonin as a Diagnostic and Prognostic Marker in Patients with Solid Tumors and Febrile Neutropenia - Jimeno, Antonio; García-Velasco, Adelaida; del Val, Olga; González-Billalabeitia, Enrique; Hernando, Susana; Hernández, Rosario; Sánchez-Muñoz, Alfonso; López-Martın, Ana; Durán, Ignacio; Robles, Luis; Corté-Funes, Hernán; Paz-Ares, Luis (Wiley InterScience, 2004)
Cancer patients with fever and neutropenia currently are assessed on clinical grounds only. The current study prospectively evaluated the efficacy of baseline procalcitonin (PCT) in the detection of bacteremia and in the prediction of outcome in patients with solid tumors and febrile neutropenia. METHODS. PCT levels were determined at baseline and every 48 hours in 104 patients undergoing chemotherapy who developed fever (axillary temperature 38 °C on 2 occasions or 38.3 °C in a single record) and neutropenia (absolute neutrophil count 500 cells/ L). RESULTS. The median baseline PCT values were significantly higher in patients who had microbiologically documented infections (1.24 ng/mL) compared with patients who had clinically documented infections (0.27 ng/mL) or fever of unknown origin (0.21 ng/mL; P 0.01). Accordingly, a PCT cut-off value of 0.5 ng/mL was reached more frequently in patients who had microbiologically documented infections compared with patients who had clinically documented infections or fever of unknown origin (66.7% vs. 13.4%, respectively; P 0.001). Furthermore, this threshold also was associated with an increased likelihood of treatment failure (70.0% vs. 14.9%; P 0.001). All 4 septic patients and all 5 patients who ultimately died presented PCT values 5-fold to 10-fold greater than the median values. Clinical evaluation in combination with baseline PCT assessment appeared to improve clinical risk evaluation alone. CONCLUSIONS. Baseline PCT levels were higher in patients who had febrile neutropenia with bacteremia compared with patients who had clinical infections or fever of unknown origin. PCT helped to identify patients who had microbiologic infections and patients who were at high risk of treatment failure, and PCT may constitute a complementary tool in the initial assessment of such patie
Este artículo ha sido publicado en la revista Cancer Esta versión tiene Licencia Creative Commons CC-BY-NC-ND Aportamos pdf que hemos recibido de la revista ante nuestra solicitud de postprint, con permiso de la revista "Thank you for reaching out. The article can be accessed and downloaded here: https://acsjournals.onlinelibrary.wiley.com/doi/full/10.1002/cncr.20275
Keywords: Cáncer - Diagnóstico; Clinical evaluation; Febrile neutropenia; Procalcitonin; Risk assessment; Solid tumors